Оценки для распределения супремума одного класса случайных процессов - Булдыгин, В.В.; Козаченко, Ю.В. (Український математичний журнал, 1993)
Exponential estimates of "tails" of supremum distributions are found for a certain class of pre-Gaussian random processes. The results obtained are applied to quadratic forms and to the processes that can be represented as stochastic integrals of processes with independent increments.